Pengaruh Kompensasi, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Jakarta Timur - Fitri Indah Febriani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Publikasi Ilmu Manajemen, 2024)
This research aims to analyze and understand the influence of compensation, motivation, and work environment on employee performance within a company. The study was conducted using a quantitative approach involving respondents from various hierarchical levels working in companies located in East Jakarta. There were 100 respondents involved, enabling the measurement of compensation levels, motivation, work environment, and employee performance. The data analysis technique employed in this research was SEM PLS (Structural Equation Modeling - Partial Least Squares), performed using SmartPLS 4.0 software. The data analysis methods encompassed measurement model analysis, structural model analysis, and hypothesis testing of direct influences. The results of the data analysis indicate that employee compensation has a significant positive influence on employee performance. Motivation also exhibits a significant positive impact on employee performance. A positive and significant effect on improving employee performance is observed with a favorable work environment. Additionally, the compensation variable was found to have a significant positive influence on employee performance. These findings hold crucial implications for organizational practitioners in designing policies and programs related to the development of compensation, motivation, and work environments to encourage employees to deliver maximum performance for the company.